Willingness to migrate-a potential effect of burnout? A survey of Hungarian physicians - Zsuzsa Győrffy; Diana Dweik; Edmond Girasek (BMC, 2018)
Abstract Background Burnout worldwide and migration of caregivers are among the most important challenges of the twenty-first century health care. Methods Quantitative, online survey of Hungarian physicians (n = 4 784) was performed in 2013. A link to an anonymous, self-administered questionnaire was sent to all potential participants, namely to the registered members of the Hungarian Medical Chamber with a valid e-mail address. Linear regression analysis was used to determine the risk factors of burnout. The association between physicians' burnout and their willingness to migrate was determined by binary logistic regression analysis. Results Moderate/mild level of personal accomplishment was detected in 65% of respondents, whereas moderate/severe level of emotional exhaustion and depersonalization was detected in 49% and 46%, respectively. Single male physicians younger than 35 composed the cohort with the highest risk for developing burnout. Higher daily working hours and multiple workplaces contribute to the risk of developing burnout. According to logistic regression analysis, the intention to work abroad was affected by the emotional exhaustion dimension of burnout (OR = 1.432) and depersonalization had a tendency to have an impact on the willingness to migrate. Conclusions We assume that there is a circular causality between burnout and the willingness to migrate. Burnout increases the willingness to work abroad, whereas contemplating migration might evoke a certain degree of depersonalization in caregivers who are in a dilemma.